Penerapan Konseling Kelompok Adlerian Untuk Mengurangi Rasa Rendah Diri Siswa Obesitas - Rahima, Raja; Neviyarni, Neviyarni; Daharnis, Daharnis (Konselor, 2015)
Inferiority is one of psychological disorder of student’s obesity. One of the approach that can be used to reduce the inferiority of student’s obesity is Adlerian group counseling. Theorically, Adler discusses physical condition as a factor causing inferiority of humans. This study is aimed to: (1) describe the inferiority of student’s obesity before and after being given the Adlerian group counseling; (2) effectiveness of Adlerian group counseling to reducing inferiority of student’s obesity. This study is conducted by using quantitative method, that is quasi experiment, the one group pre-test post-test design is used. The selection of subjects in this study using non-random sampling technique with purposive sampling method. The subjects were 12 student’s obesity with high and medium levels of inferiority. This study was conducted in SMPI Khaira Ummah Padang from October to November 2014. The instrument used Likert scale. The analyzed was using non-parametric statistical technique that is Wilcoxon’s test. The findings of this study indicate that: (1) there is the difference of inferiority of the student’s obesity before and after being given treatment of Adlerian group counseling. Inferiority of student’s obesity has descreased after being given treatment; (2) Adlerian group counseling effective to reducing inferiority of student’s obesity. Adlerian group counseling can significantly to reduce inferiority student’s obesity, beneficial to further reduce the problem of inferiority due to other physical conditions